A New Species of the Genus Lejeunea Lib. (Marchantiophyta, Lejeuneaceae) From Nilgiri Hills, Western Ghats, India - Verma, Praveen Kumar; Rawat, K. K.; Alam, Afroz (Indian Forester, 2019)
No Abstract.